A model for simultaneous location and coordination of protective devices in radial distribution networks. Issue 19 (24th May 2021) - de la Barra, Joaquín; Angulo, Alejandro; Gil, Esteban
Abstract: Upgrading protection schemes in distribution networks can help electric utilities to improve the reliability of their supply. Fuses and reclosers are still the primary protective devices used in distribution grids, and their optimal allocation allows isolating faults with the least number of interrupted customers. However, most models used to select and locate protective devices optimally do not consider their coordination or rescue schemes for the fuses, resulting in unfeasible or impractical solutions. This paper presents a mixed‐integer linear program model for the simultaneous selection, localization, and coordination of protective devices (reclosers and fuses), considering the fuses' rescue schemes based on electrical criteria. Local reliability indices and economic penalties for violating minimum standards are integrated into the model, thereby providing new decision‐making elements. The proposed approach is tested in different distribution networks to showcase its key features. Computational experiments show that the proposed model can satisfactorily handle the trade‐off between costs and reliability.